O programa sala de leitura e seus reflexos nas histórias de leitura de alunos e professores de uma escola estadual paulista - Gimenez, Queila Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper is an investigation about the relations between the Room to Read Project, introduced by the state government in a state school in the countryside of the state of São Paulo in 2009, and the reading background of the teachers responsible for the Room as a reading mediator, and the reading background of three students chosen by those teachers due to the frequency they attend this Room. By analyzing qualitative data, we tried to understand how the Room to Read works, and the profile of this school community was studied considering the formation of its cultural identity and relating it with the reading as a cultural product. In order to carry out this investigation, interactions were made by means of interviews recorded with the teachers responsible for the Room to Read and with the chosen students. The interviews were analyzed, qualitatively investigating the participant's reading stories and experiences, and based on the theoretical and methodological approaches of Clandinin and Connelly's (2011) narrative research. In order to understand what those Canadian authors refer to, we relied on Gadamer's (1997) philosophical hermeneutics, trying to analyze how much of those reading experiences can be (or cannot be) related to the frequency the students go to Room to Read during the daily school routine and how those experiences help (or do not help) their identity formation within the school. We also relied on Soares's (2006; 2010) and Kleiman's (2010) studies on literacy, on anthropologist Michèle Petit's (2008; 2010) records about reading experiences, and on Roger Chartier's (1996; 1999) contributions related to reading, books and cultural practices, which are in line with Lipovetsky and Serroy's (2011) world-culture approach. Regarding identity formation and its relation with the reading role, we relied on Bauman's (2005) e Hall's (2011; 2013) work concerning identity...

O presente trabalho representa uma investigação acerca das relações entre o Programa Sala de Leitura, implantado em 2009 numa escola estadual do interior paulista, pelo governo do Estado, e a formação leitora das professoras responsáveis pela Sala, na condição de mediadoras de leitura, e de três alunos, indicados por essas professoras pela assiduidade com que frequentam esse espaço. Por meio de uma análise qualitativa de dados, procurei compreender o funcionamento dessa Sala de Leitura, além de analisar o perfil da comunidade escolar em questão, considerando a constituição de sua identidade cultural e relacionando-a com a questão da leitura, enquanto produto cultural. Para desenvolver tal investigação, foram efetuadas interações, por meio de entrevistas gravadas, com as professoras responsáveis pela Sala de Leitura e com os alunos selecionados. Procedi a uma análise dessas entrevistas, investigando as histórias e experiências de leitura dos participantes, de forma qualitativa, fundamentada na concepção teórico-metodológica da pesquisa narrativa de Clandinin e Connelly (2011). A fim de chegar à compreensão a que se referem os autores canadenses, amparei-me na hermenêutica filosófica de Gadamer (1997), procurando analisar em que medida essas experiências de leitura podem (ou não) estar relacionadas à presença da Sala de Leitura no cotidiano da escola e de que forma elas contribuem (ou não) para a construção das identidades que se constituem dentro daquele espaço escolar. Apoiei-me nos estudos sobre o letramento, desenvolvidos por Soares (2006; 2010) e Kleiman (2010), nos registros sobre experiências de leitura, da antropóloga Michèle Petit (2008; 2010) e nas contribuições de Roger Chartier (1996; 1999) sobre leitura, livros e práticas culturais, em diálogo com a concepção de cultura-mundo, desenvolvida por Lipovetsky e Serroy (2011). Quanto à questão da...
Keywords: Leitura; Interesses na leitura; Bibliotecas e escolas; Reading